WOMEN AND PUBLIC POLICIES: ADVANCES AND RETROCESSES IN TIMES OF RESISTANCE - Reis, Ana Terra [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2019)
This article aims to present elements that show the progress achieved and the setbacks consolidated in the first two decades of this millennium, especially with regard to public policies that deal with gender issues. In our introduction, we warned about the challenges of acting as a researcher, mother and activist, and then analyzed the participation of women in some institutional spaces, as well as some of the public policies that provided steps towards the construction of female autonomy. Finally, we point out the need to move forward in building a more just and fraternal society based on class resistance, with a sociability that overcomes gender oppressions.
Keywords: Women; public policies; State